Changes of reproductive indices of the testis due to Trypanosoma evansi infection in dromedary bulls (Camelus dromedarius): Semen picture, hormonal profile, histopathology, oxidative parameters, and hematobiochemical profile (Journal of Advanced Veterinary and Animal Research, 2020)
Objectives: This study was designed for the investigation of the effect of infection by Trypanosoma evansi on the changes of reproductive indices of the testis, causing reproductive failure in dromedary bulls (Camelus dromedarius).  Material and methods: Seventy-five bulls were used for monitoring of the changes in the semen characteristics, reproductive hormones, hematobiochemical profiles, histopathological characters in the testis, and oxidative biomarkers. The animals were divided into two groups. Group A represented the uninfected or control group, while group B represented the infected group. Group B was again divided into two subgroups, such as acute and chronic infected animals.  Results: Results showed that the semen analysis of infected camels revealed the presence of alterations in the morphology of sperms, especially the heads and tails, as compared to control animals. The hormonal profile indicated a significant decrease in the luteinizing hormone, follicle-stimulating hormone, and testosterone levels, accompanied by the rise in the cortisol level in infected camels compared with the negative control. The histopathology and testicular degeneration were found to be associated with other disorders in infected camels. The oxidative profile and protein oxidation were promoted in infected testicles, indicating the occurrence of harmful effects in the cell.  Conclusion: It is concluded that T. evansi infection in dromedary bulls causes severe damage to the testicular tissue and decreases the reproductive hormone levels associated with severe morphological disorders in sperms due to oxidative stress resulting from the infection. All these findings indicate that T. evansi can cause reproductive failure and fertility damage.J. Adv. Vet. Anim. Res., 7(3): 537-545, Sep 2020http://doi.org/10.5455/javar.2020.g451